Usage of Electronic Resources by the Students of Mahatma Gandhi University, Kottayam, Kerala - Jomy Jose
The study aims to provide an overview about the use of e-resources by students in Mahatma Gandhi (MG)University, Campus Kottayam .Survey method was used as the research instrument for this study. A questionnaire survey was conducted to collect the information regarding the use of e-resources, frequency of use of e-resources, purpose of using e- resources.The questionnaire titled ‘Electronic Resources Usage of Students at MG University, Campus,Kottayam’ has been used for data collection. Questionnaires were distributed randomly to the users. A total of 600 questionnaires were distributed to collect the primary data out of which 584 questionnaires were found usable for analysis. Study found that more than 9.42% respondents use different e- resources when necessary, 46.92% occasionally and rest of them ( 43.66% )very often.Online databases (35.10 % ) and UGC Info- net (25.34 %) are the major sources of e resources .DOAJ Directory of Open Access Journals comes in third position (15.58 %) and WWW Sources (14.73